2022
DOI: 10.3390/machines10100901
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Manufacturing Parameters of DLP Machine by Taguchi Method and Desirability Approach

Abstract: With less manufacturing time and less photosensitive resin consumed, Digital Light Processing of the bottom-up process is more forward-looking than the top-down one in terms of 3D printing technology. In view of differences in the optimization of machine printing parameters for objectives with different quality requirements, this paper discusses how the control factors consisting of machine printing parameters can obtain objects with a high quality through an experimental design with full considerations of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In addition, it reduces experiment time and costs [15]. Another study by Yang [16], and Oemar et al [17], approved that by Taguchi method found that speed was the important parameter affecting the output of dimensional tolerance and separation force in 3D additive manufacturing, and chemical reagent concentration and activation temperature in the activated carbon production from rubber seed shell, respectively.…”
Section: Figure 1: Illustration Of the Milling Process In Cnc Machiningmentioning
confidence: 99%
“…In addition, it reduces experiment time and costs [15]. Another study by Yang [16], and Oemar et al [17], approved that by Taguchi method found that speed was the important parameter affecting the output of dimensional tolerance and separation force in 3D additive manufacturing, and chemical reagent concentration and activation temperature in the activated carbon production from rubber seed shell, respectively.…”
Section: Figure 1: Illustration Of the Milling Process In Cnc Machiningmentioning
confidence: 99%